Intuitionistic Fuzzy AHP and WASPAS to Assess Service Quality in Online Transportation - Annisa Kesy Garside; Rara Putri Ayuning Tyas; Rahmad Wisnu Wardana (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
Indonesia is currently entering a new normal era; this requires people to adapt to the clean-living habit in accordance with health standards in order to carry out normal activities. At the same time, online transportation services have reopened for activity. The service quality provided by online ride-hailing companies (i.e., ojek) such as Gojek, Grab, and Maxim must now consider matters relating to user safety. This study proposes Multi Criteria Decision Making (MCDM) as a method for assessing the service quality of online transportation service providers and uses the Pandemic-SERVQUAL 4.0 model. Pandemi-SERVQUAL 4.0 model adds two new criteria, namely